2009
DOI: 10.1016/j.cmet.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence Supporting a Critical Role of Endothelial Caveolin-1 during the Progression of Atherosclerosis

Abstract: SUMMARY The accumulation of LDL-derived cholesterol in the artery wall is the initiating event that causes atherosclerosis. However, the mechanisms that lead to the initiation of atherosclerosis are still poorly understood. Here, by using endothelial cell-specific transgenesis of the caveolin-1 (Cav-1) gene in mice, we show the critical role of Cav-1 in promoting atherogenesis. Mice were generated lacking Cav-1 and apoE but expressing endothelial-specific Cav-1 in the double knockout background. Genetic ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
163
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 33 publications
(34 reference statements)
8
163
0
Order By: Relevance
“…Another key finding of our work stems from the observation that CavNOxin-induced NO upregulation was able to attenuate aortic and endothelial VCAM-1 expression, which correlated closely with the reduction in leukocyte/monocyte adhesion to the vascular wall and to cultured endothelial cells in diabetic and inflammatory (TNF-a) settings, lending credence to previous studies that demonstrated decreased leukocyte recruitment and VCAM-1 expression in Cav-1 KO tissues (38)(39)(40). Furthermore, increased eNOS activity has been associated with the downregulation of adhesion molecules, in particular VCAM-1 (19), and our data suggest that this can be achieved specifically through endogenous eNOS in a compensatory manner because hyperglycemia is a potent inducer of leukocyte-endothelial interactions (13,41).…”
Section: Discussionsupporting
confidence: 58%
“…Another key finding of our work stems from the observation that CavNOxin-induced NO upregulation was able to attenuate aortic and endothelial VCAM-1 expression, which correlated closely with the reduction in leukocyte/monocyte adhesion to the vascular wall and to cultured endothelial cells in diabetic and inflammatory (TNF-a) settings, lending credence to previous studies that demonstrated decreased leukocyte recruitment and VCAM-1 expression in Cav-1 KO tissues (38)(39)(40). Furthermore, increased eNOS activity has been associated with the downregulation of adhesion molecules, in particular VCAM-1 (19), and our data suggest that this can be achieved specifically through endogenous eNOS in a compensatory manner because hyperglycemia is a potent inducer of leukocyte-endothelial interactions (13,41).…”
Section: Discussionsupporting
confidence: 58%
“…It was reported that LDL-derived cholesterol, the major component of atherosclerotic plaque, enters the subendothelial space through the caveolaemediated pathway (Sun et al 2010). Results from cav-1 (caveolin-1, the key structural protein of caveolae)-deficient mice indicated that cav-1 in endothelium is essential in the translocation of LDL-derived cholesterol into the vessel wall and in the development of atherosclerosis, and this result was further confirmed in apoE-/-mice (Fernandez-Hernando et al 2009. On the other side, vascular endothelial growth factor (VEGF), one of the strongest hyperpermeability inducers (Senger et al 1990), plays a critical role in both physiological and pathological hyperpermeability (Bates and Harper 2002).…”
Section: Introductionsupporting
confidence: 55%
“…On the other side, Cav-1 is the key structural protein of caveolae (Drab et al 2001). Reexpression of endothelial cav-1 in cav-/-mice demonstrated that cav-1 is indispensable to the transportation of LDL-derived cholesterol to the subendothelial space (Fernandez-Hernando et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…10 -12 In the cardiovascular system, caveolae and Cav-1 show an important role in the proliferation and migration of smooth muscle cells, 13 regulation of NO production and vascular permeability, 8,14 angiogenesis, [15][16][17] and atherosclerosis. 18,19 Cav-1-deficient mice develop cardiac hypertrophy, hypercholesterolemia, and hypertriglyceridemia and have increased tumor microvascular permeability, angiogenesis, and growth. 17 Interestingly, the absence of Cav-1 reduces the progression of atherosclerosis.…”
mentioning
confidence: 99%
“…19 Very recently, we showed, using a genetic model, that endo-thelial caveolae are essential for the progression of atherosclerosis. 18 Mechanistically, endothelial Cav-1 and caveolae are critical for LDL infiltration in the artery wall, NO production, and macrophage accumulation, all events necessary for atherogenesis. 18 Although Cav-1-null mice are useful to delineate the importance of caveolae in atherosclerosis, there are additional problems that are difficult to dissect, because loss of Cav-1 abolishes both caveolae organelles as well as Cav-1-mediated signaling pathways.…”
mentioning
confidence: 99%